2022
DOI: 10.1097/mpa.0000000000002024
|View full text |Cite
|
Sign up to set email alerts
|

Serum n-3 Polyunsaturated Fatty Acids and C-Reactive Protein Concentrations Are Inversely Associated in Patients With Alcoholic Chronic Pancreatitis

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…2,22,40 Several studies have shown FAs like linoleic acid as well as other fatty acids in its metabolic pathway are dysregulated in patients with CP who had a history of excessive alcohol consumption compared to healthy controls. 7,41,42 In our study, the relative abundance of linoleic acid was decreased and oleic acid was increased due to alcohol use, and only linoleic acid was affected by a history of smoking in CP. Linoleic acid metabolism can result in an increase of prostaglandins that promote inflammation.…”
Section: Discussionmentioning
confidence: 46%
“…2,22,40 Several studies have shown FAs like linoleic acid as well as other fatty acids in its metabolic pathway are dysregulated in patients with CP who had a history of excessive alcohol consumption compared to healthy controls. 7,41,42 In our study, the relative abundance of linoleic acid was decreased and oleic acid was increased due to alcohol use, and only linoleic acid was affected by a history of smoking in CP. Linoleic acid metabolism can result in an increase of prostaglandins that promote inflammation.…”
Section: Discussionmentioning
confidence: 46%
“…Substance abuse is another important etiologic risk factor for developing CP. Several studies have shown polyunsaturated FAs (PUFAs) like linoleic acid are decreased and MUFAs like oleic acid are increased in patients with CP who had a history of excessive alcohol consumption compared with healthy controls 7,49,50 ; however, many of these studies do not address how smoking affects FAs in patients who already have CP. In our study, we confirm that linoleic acid decreased, and oleic acid increased with alcohol use in patients with CP.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study concluded that the neutrophil-to-lymphocyte ratio along with serum CRP levels at 48 h could be suitable for predicting SAR, and that CRP was a good predictive marker for mortality [ 365 , 366 ]. CRP levels can be higher in patients with chronic pancreatitis and type 2 DM than those with isolated chronic pancreatitis, and also, an inverse correlation has been reported for CRP and subjects with alcoholic chronic pancreatitis [ 367 , 368 ]. Moreover, a study showed that CRP can reliably predict the risks of pancreatic fistula, pancreas-specific complications, and hospital readmission, and should be considered for such conditions post-pancreaticoduodenectomy [ 369 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%